Assessment of the Institutionalization of the Golkar Party in Sungai Penuh City in the 2024 Election - Iga May Tandayun; Dimas Subekti; Zakly Ahmad Hanafi; Ian Pasaribu (Parapolitika: Journal of Politics and Democracy Studies, 2026)
This study employs the party institutionalization perspective to examine the increase in the vote share of the Golkar Party in Sungai Penuh City in the 2024 elections. This research uses a qualitative method with a case study approach. Data were collected through in-depth interviews with 12 informants consisting of party elites, legislative candidates, and grassroots cadres, and complemented by document analysis. The findings of this study explain that the increase in the vote of the Sungai Penuh City Golkar party in the 2024 elections was due to good institutionalization factors as shown by three indicators ranging from roots in society ((the party has a mass base and a strong image in the community), level of organization (organizational tools that consistently work for the benefit of the party at every level of management) and coherence (cohesiveness of party members). However, there is a note on the autonomy indicator (independent in decision-making) that, although the Golkar party has internal rules that uphold autonomy and independence, the practice in the field shows that decisions are still dominated by the party's internal elite in a closed manner. Therefore, while institutionalization appears to have contributed to Golkar’s electoral performance in Sungai Penuh City, the findings should be understood as indicative rather than strictly causal, as other contextual and political factors may also have played a role. This study contributes to enriching the literature on party institutionalization at the local level in post-Reformasi Indonesia, particularly in the period leading up to the 2024 elections. Nonetheless, the study has limitations, including its single-case design, the potential bias inherent in elite-based interviews, and the limited generalizability of its findings beyond the specific local context examined.